Understanding the Motivations, Satisfaction, and Retention of Landowners in Private Land Conservation Programs. Issue 4 (18th January 2015) - Selinske, Matthew J.; Coetzee, Jan; Purnell, Kerry; Knight, Andrew T.
Abstract Private land conservation is an increasingly popular approach to protect critical biodiversity. In the Western Cape Province of South Africa private land conservation is the focal strategy for CapeNature, the provincial conservation agency. Despite its importance, little is known about the drivers of landowner participation in the CapeNature program and how these varied motivations influence participant satisfaction and retention. Our psychometric survey of 75 enrolled landowners found that the highest ranked motivations to participate were Conservation and Place Attachment but Social Learning had a stronger influence on program satisfaction. Landowners participate to fulfill a motivation or set of motivations but their satisfaction and commitment may hinge on other unforeseen motivations or factors. Understanding the relationship between motivations, satisfaction, and commitment is necessary for a successful retention strategy in any conservation program, especially on private lands where success depends on landowner commitment. This research was incorporated into improving CapeNature's program delivery.